Organic resin coating film as well as preparation method and application thereof
By loading an organic resin coating onto a polyester base film to form an embedded "rivet" structure, the problems of insufficient corrosion resistance, heat resistance and peel strength of polyester film composite current collectors are solved, and the structural stability and processing performance are improved.
Patent Information
- Application Number
- CN202511577049.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-23
AI Technical Summary
Existing composite current collectors based on polyester films have shortcomings in corrosion resistance, heat resistance, and peel strength, resulting in low production yield, poor structural stability, and easy detachment of the metal layer.
An organic resin coating is loaded on one or both sides of a polyester base film. The coating contains organic resin, curing agent, inorganic filler and surfactant. By controlling the surface roughness of the coating between 200nm and 400nm, an embedded "rivet" structure is formed between the conductive metal layer and the coating to improve the bonding force.
It improves the structural stability and processing performance of composite current collectors, prevents base film wrinkling, metal layer peeling and electrolyte corrosion, and enhances high temperature resistance and surface adhesion.
Smart Images

Figure CN121378871A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite current collector technology, and relates to an organic resin coated film, its preparation method and application, specifically to an organic resin coated film, its preparation method and a composite current collector. Background Technology
[0002] Currently, composite current collectors based on polymer thin films are receiving widespread attention and application in the new energy industry. Composite current collectors consist of a base film layer and metal layers disposed on both sides of the base film layer.
[0003] Among the many composite current collectors based on polymer films, those based on polyester films are the most common and represent the current mainstream approach. However, the following problems still exist in the preparation of composite current collectors using polyester films as the substrate: ① The poor corrosion resistance of polyester films leads to swelling of the base film and high-temperature cycling during use; ② Poor heat resistance during use, i.e., excessive shrinkage of the polyester film at higher temperatures causes separation between the base layer and the metal layer; ③ Insufficient peel strength and poor adhesion between the metal layer and the polyester film layer of the composite current collector.
[0004] Therefore, in this field, there is a desire to develop an organic resin coating film that has good corrosion resistance, excellent heat resistance, and high surface adhesion. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide an organic resin coated film, its preparation method, and its applications. Specifically, it provides an organic resin coated film, its preparation method, and a composite current collector, aiming to solve the problems of low production yield and high overall cost caused by the poor heat resistance, easy wrinkling, and poor corrosion resistance of the base film in the preparation of existing polyester film-based composite current collectors. It also addresses industry pain points such as easy metal layer detachment, poor structural stability, poor high-temperature resistance, and poor resistance to electrolyte corrosion in composite current collectors prepared from such base films. The organic resin coated film provided by the present invention has high surface adhesion, corrosion resistance, and high-temperature resistance, thereby improving the structural stability and processing performance of the composite current collector.
[0006] To achieve this objective, the present invention employs the following technical solution:
[0007] In a first aspect, the present invention provides an organic resin coated film, the organic resin coated film comprising a polyester base film and an organic resin coating disposed on one or both sides of the polyester base film;
[0008] The organic resin coating comprises organic resin, curing agent, inorganic filler, and surfactant;
[0009] The average surface roughness Ra of the organic resin coating is 200nm~400nm, for example, it can be 200nm, 220nm, 240nm, 250nm, 260nm, 280nm, 300nm, 320nm, 340nm, 350nm, 360nm, 380nm, 400nm, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0010] This invention improves the thermal stability, corrosion resistance, and surface adhesion of a polyester base film by loading an organic resin coating on one or both sides. When used in a composite current collector, it can effectively prevent wrinkling and shrinkage of the base film, peeling of the metal layer, corrosion of the composite current collector by the electrolyte, and circulation failure.
[0011] This invention controls the average surface roughness Ra of the organic resin coating between 200nm and 400nm, ensuring better deposition and adhesion of metal particles to the coating surface when the organic resin coating is used in composite current collectors, thereby improving the peel strength between the conductive metal layer and the coating. The bonding force between the conductive metal layer and the organic resin coating mainly comes from the embedded "rivet" structure formed by the conductive metal layer and the rough coating. If the average surface roughness of the organic resin coating is too low, the coating surface tends to be smooth, the formed "rivet" structure is shallow, the bonding force between the conductive metal layer and the coating is weak, and the peel strength is not high. If the average surface roughness of the organic resin coating is too high, there are too many micropores. On the one hand, the internal structure of the coating is severely damaged, making it unable to form a strong interlocking force with the conductive metal layer. The "rivets" formed with the conductive metal layer are more likely to break. On the other hand, if the "rivets" are too dense, the organic resin coating between the "rivets" is also more likely to break, thus the peel strength will be even lower.
[0012] In this invention, the test method for the surface average roughness Ra of the organic resin coating is as follows: Sample size Securely attach the sample to the metal sample holder of the AFM using double-sided conductive tape. Ensure the sample is flat, without wrinkles or air bubbles. Select Tapping Mode / Intermittent Contact Mode and use a silicon probe or silicon nitride probe with a high resonant frequency and high elastic constant. Standard Tapping Mode probes (such as the RTESA series) are sufficient. Perform a large-area scan first (e.g., ...). Then perform a small-area scan (such as...) To obtain more accurate individual particle morphology and roughness data, the roughness (Ra) value should be calculated on a small-scale scan image to exclude the effects of large-scale curvature. Set a sufficient number of pixels and a scan rate of 0.5-1.0 Hz. Perform plane fitting (Flattening) on the acquired height map to eliminate the tilt or curvature of the sample itself, and then calculate the roughness Ra.
[0013] Preferably, the organic resin includes any one or a combination of at least two of the following: epoxy resin, acrylic resin, hydrocarbon resin, triazine resin, polytetrahydrofuran resin, fluororesin, phenoxy resin, polyvinyl acetal resin, polyimide resin, polyamide-imide resin, polysiloxane resin, polyether-imide resin, polysulfone resin, polyethersulfone resin, and polyphenylene ether resin, with epoxy resin being the most preferred. Epoxy resin has good corrosion resistance and heat resistance, and as the main coating material, it is easier to roughen (modify) the surface of the coating, thereby improving the adhesion between the film and the metal layer.
[0014] Preferably, based on the total mass of the organic resin coating as 100%, the proportion of the organic resin is 20% to 40%, for example, it can be 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0015] Preferably, the epoxy resin includes at least two of the following: bisphenol type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, phenol type epoxy resin, and phenolic type epoxy resin.
[0016] As a preferred embodiment of the present invention, by using at least two epoxy resins with different chemical structures, synergistic crosslinking effects occur between the different chemical structures during the crosslinking and curing process of the epoxy groups, providing different physical properties. Bisphenol-type epoxy resin increases the surface tension of the organic resin coating, facilitating the deposition and adhesion of subsequent metal layers. Biphenyl-type epoxy resin provides the organic resin coating with higher tensile strength, elongation at break, heat resistance, and chemical corrosion resistance, while also reducing the viscosity of the organic resin mixture, thus facilitating coating. Naphthalene-type epoxy resin provides the organic resin coating with higher chemical stability and corrosion resistance. Phenolic-type epoxy resin exhibits good adhesion, providing the organic resin coating with higher adhesion and mechanical strength. Phenolic-type epoxy resin provides the organic resin coating with high heat resistance. The present invention achieves the desired effect through the synergistic effect between epoxy resins with different chemical structures.
[0017] Preferably, based on the total mass of the epoxy resin (100%), the proportion of bisphenol-type epoxy resin is 40% to 75%, for example, it can be 40%, 42%, 44%, 45%, 46%, 48%, 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, etc., but is not limited to the listed values; other unlisted values within this range are also applicable. The proportion of biphenyl-type epoxy resin is 5% to 40%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%. The percentages are 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, etc., but are not limited to the listed values. Other unlisted values within this range also apply. The proportion of naphthalene-type epoxy resin is 0% to 35%, for example, it can be 0 (i.e., no epoxy resin added), 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%. 28%, 30%, 32%, 34%, 35%, etc., but not limited to the listed values; other unlisted values within this range also apply. The proportion of phenolic epoxy resin is 0% to 40%, for example, it can be 0 (i.e., no epoxy resin added), 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, etc., but not limited to the listed values; this range of values... Other unlisted values within this range also apply. The proportion of phenolic epoxy resin is 0% to 50%, for example, it can be 0 (i.e., no epoxy resin of this type), 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, 46%, 48%, 50%, etc., but is not limited to the listed values. Other unlisted values within this range also apply.
[0018] For example, the bisphenol-type epoxy resin includes any one or a combination of at least two of bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol S-type epoxy resin, bisphenol AF-type epoxy resin, bisphenol AD-type epoxy resin, bisphenol A phenolic epoxy resin, and bisphenol F phenolic epoxy resin; the biphenyl-type epoxy resin includes any one or a combination of at least two of tetramethylbiphenyl-type epoxy resin, crystalline biphenyl-type epoxy resin, phenolic biphenyl-type epoxy resin, biphenyl aryl-type epoxy resin, and biphenyl alkyl-type epoxy resin; the naphthalene-type epoxy resin includes any one or a combination of at least two of EBA-65 naphthalene-type epoxy resin, 2,2'-diglycidyl ether-1,1'-binaphthyl, and naphthol phenolic epoxy resin. The phenolic epoxy resin includes any one or at least two of the following: phenol-aralkyl epoxy resin, dicyclopentadiene phenolic epoxy resin, phenolic epoxy resin, waterborne phenolic epoxy resin, aminophenolic epoxy resin, organosilicon-modified multifunctional epoxy adhesive, tetraphenolic ethane epoxy resin, resorcinol-type phenolic epoxy resin, and o-cresol linear phenolic epoxy resin; the phenolic epoxy resin includes any one or at least two of the following: bisphenol A phenolic epoxy resin, bisphenol F phenolic epoxy resin, o-cresol-type phenolic epoxy resin, cresol-type phenolic epoxy resin, naphthol-type phenolic epoxy resin, linear phenolic epoxy resin, phenolic epoxy resin, and triphenylmethane-type epoxy resin.
[0019] Preferably, the epoxy equivalent of the epoxy resin is 50 to 5000, for example, it can be 50, 80, 100, 200, 300, 500, 600, 800, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable, and it is further preferred to be 100 to 1000. When the epoxy equivalent of the epoxy resin is within this range, the cross-linking of the cured product in the organic resin mixture slurry is more complete.
[0020] Preferably, the weight-average molecular weight of the epoxy resin is 100 to 5000, for example, it can be 100, 200, 300, 500, 600, 800, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable, and it is further preferred to be 500 to 1500.
[0021] Preferably, the curing agent includes any one or a combination of at least two of the following: phenol-based curing agents, naphthol-based curing agents, reactive ester-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, and carbodiimide-based curing agents; more preferably, it includes at least one of the following: phenol-based curing agents, reactive ester-based curing agents, and cyanate ester-based curing agents.
[0022] Preferably, the phenol-based curing agent includes a curing agent containing a triazine backbone and a phenolic resin structure. The organic resin coating formed by the cross-linking and curing reaction of this type of curing agent with organic resin has good heat resistance. When applied to composite current collectors, it has a strong bonding force with the conductive metal layer.
[0023] Preferably, the active ester-based curing agent includes any one or a combination of at least two of the following: an active ester compound containing a dicyclopentadiene-type diphenol structure, an active ester compound containing a naphthalene structure, an active ester compound containing an acetylated form of phenolic resin, and an active ester compound containing a benzoyl form of phenolic resin.
[0024] Preferably, the cyanate-based curing agent includes any one or a combination of at least two of the following: bisphenol A dicyanate, polyphenol cyanate, oligomeric (3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate-phenyl)propane, 1,1-bis(4-cyanate-phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate-phenyl-1-(methylethylene))benzene, bis(4-cyanate-phenyl) sulfide, bis(4-cyanate-phenyl) ether, and other difunctional cyanate resins, as well as polyfunctional cyanate resins derived from phenolic resins and cresolic resins.
[0025] Preferably, the curing agent accounts for 5% to 10% of the total mass of the organic resin coating, for example, 5%, 6%, 7%, 8%, 9%, 10%, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0026] Preferably, the inorganic filler includes any one or a combination of at least two of the following: silicon dioxide, alumina, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, calcined kaolin, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, titanium dioxide, silicon carbide, and zirconium oxide.
[0027] More preferably, considering the compatibility and dispersibility of inorganic fillers in organic resin mixtures, the inorganic filler is further preferably silica, which can be more uniformly dispersed in the organic resin matrix.
[0028] More preferably, in order to improve the adhesion of the organic resin coating to the polyester film surface and the smoothness of the coating surface, while ensuring sufficient mechanical strength, the silica is further preferably spherical silica.
[0029] Because the spherical silica distributed in the organic resin has strong fluidity, even after curing to form a reinforced network structure, it can still ensure that the organic resin coating has good flexibility and bending ability, thus improving the performance of subsequent applications.
[0030] Furthermore, considering the improvement of the dispersibility of inorganic fillers in organic resins and the smoothness of coatings, the average particle size of the inorganic filler is 50nm~350nm, for example, it can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable, and it is further preferred to be 100nm~200nm.
[0031] Furthermore, considering the need to reduce the minimum melt viscosity of the organic resin coating and improve its flexibility, the specific surface area of the spherical silica is 1 m². 2 / g~45m 2 / g, for example, could be 1m 2 / g、2m 2 / g、3m 2 / g、5m 2 / g、8m 2 / g, 10m 2 / g, 15m 2 / g、20m 2 / g、25m 2 / g、30m 2 / g、35m 2 / g、40m 2 / g、45m 2 / g, etc., but not limited to the listed values; other unlisted values within this range also apply, with 10m being a further preferred value. 2 / g~40m 2 / g.
[0032] Preferably, the spherical silica comprises spherical silica with a surface treated with a coupling agent to improve its wettability and dispersibility. The coupling agent (e.g., a silane coupling agent) forms a chemical bond with the hydroxyl groups on the surface of the inorganic filler through a reaction of its hydrophilic end group, while its lipophilic end group forms a physical or chemical interaction with the organic resin matrix, establishing a "bridge" between the organic and inorganic phases, thereby significantly enhancing the interfacial bonding force.
[0033] Preferably, based on the total mass of the organic resin coating as 100%, the proportion of the inorganic filler is 50% to 80%, for example, it can be 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, etc., but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0034] Preferably, the surfactant comprises any one or a combination of at least two of aminosilane compounds, aminosiloxane compounds, alkylsilane compounds, and alkylsiloxane compounds. The main function of the surfactant is to disperse the inorganic filler more uniformly in the organic resin mixture slurry.
[0035] Preferably, the surfactant comprises a diethylaminomethyltriethoxysilane compound.
[0036] Preferably, based on the total mass of the organic resin coating as 100%, the surfactant accounts for 0.5% to 2%, for example, it can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, etc., but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0037] Preferably, the organic resin coating may also include other additives as needed.
[0038] Preferably, the other additives include any one or a combination of at least two of the following: curing accelerators, flame retardants, thickeners, and defoamers.
[0039] Preferably, based on the total mass of the organic resin coating (100%), the curing accelerator accounts for 0-3%, for example, 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc., but is not limited to the listed values; other unlisted values within this range are also applicable. The flame retardant accounts for 0-10%, for example, 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%. The percentages are 0%, 9.5%, 10%, etc., but not limited to the listed values. Other unlisted values within this range also apply. The percentage of the thickener is 0-1%, for example, it can be 0, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, etc., but not limited to the listed values. Other unlisted values within this range also apply. The percentage of the defoamer is 0-0.5%, for example, it can be 0, 0.2%, 0.3%, 0.5%, etc., but not limited to the listed values. Other unlisted values within this range also apply.
[0040] It should be noted that the proportions of all the above components in the organic resin coating are based on the assumption that the non-volatile substances in the coating after the organic resin mixture has been cured are set to 100 wt%.
[0041] Preferably, the curing accelerator comprises any one or a combination of at least two of phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators, and more preferably at least one of amine-based curing accelerators, imidazole-based curing accelerators, and metal-based curing accelerators. The curing accelerator can accelerate the curing rate of the organic resin.
[0042] Preferably, the flame retardant includes any one or a combination of at least two of the following: organophosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, organosilicon flame retardants, and metal hydroxides.
[0043] Preferably, the thickener comprises any one or a combination of at least two of the following: aqueous acrylic resin, polyurethane resin, vinyl acetate resin, hydroxypropyl methylcellulose, ethyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol; more preferably, it comprises at least one of the following: hydroxypropyl methylcellulose, ethyl cellulose, and polyvinyl alcohol.
[0044] Preferably, the defoamer includes any one or a combination of at least two of the following: silicone defoamer, mineral oil defoamer, polyether defoamer, alcohol defoamer, polyether-modified silicone defoamer, GPES type defoamer, GPE type defoamer, and polyvinyl alcohol defoamer; more preferably, alcohol defoamer and / or polyether-modified silicone defoamer.
[0045] Preferably, the polyester-based film is made of any one or a combination of at least two of the following: polyterephthalate, polymethyl methacrylate, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyurethane, polyurethane, polyvinyl acetate, polyarylate, polyethylene naphthalate (PEN), polyethylene oxide acrylate, polycarbonate, thermoplastic polyester elastomer, polybutylene succinate, and polycaprolactone; preferably, at least one of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN).
[0046] Preferably, the surface of the polyester-based film has uniformly distributed micropores.
[0047] Preferably, the porosity of the polyester-based film is 20% to 70%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable, preferably 40% to 60%.
[0048] Preferably, the pore size of the polyester base film is 50nm~300nm, for example, it can be 50nm, 60nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, etc., but it is not limited to the listed values, and other unlisted values within this range are also applicable. Larger pore sizes are more beneficial for improving the conductivity and reducing the internal resistance of the composite current collector, but the mechanical strength will also decrease, and the adhesion of the metal layer will be worse; pore sizes that are too small are not conducive to reducing the internal resistance of the composite current collector. The pore size of the polyester base film is further preferably 100nm~200nm.
[0049] The average particle size of the inorganic filler used in this invention is consistent with the pore size of the polyester base film surface, both being between 100nm and 200nm. This allows the inorganic filler in the organic resin coating to be better embedded in the micropores of the polyester base film surface, thereby improving the peel strength of the organic resin coating.
[0050] Preferably, the pore size of the polyester base film is directly proportional to its porosity; that is, the greater the porosity of the base film, the larger the corresponding pore size. Only under this condition can the difference in micropore area on the surface of different base films be relatively small, and the area of micropores on the surface of the polyester base film per square meter is controlled within 8m². 2 -10m 2 At this point, the micropores on the base film surface are relatively dense and the roughness is relatively high, which can ensure that the polyester base film has good mechanical strength and that the organic resin coating has good adhesion to the polyester base film.
[0051] It should be noted that the pore size of the polyester base film is directly proportional to its porosity. This means that within the scope of this invention, the higher the porosity of the polyester base film, the larger the proportion of micropore volume, and therefore the larger the surface pore size needs to be; conversely, the lower the porosity of the polyester base film, the smaller the proportion of micropore volume, and therefore the smaller the surface pore size needs to be. Only in this way can we ensure that different base films have similar surface properties, such as average surface roughness and micropore area. Under these conditions, the organic resin mixture slurry of this invention achieves the best coating effect. For example, when the porosity of a 4.5μm polyester base film is 60%, its pore size can be 200nm, at which point the micropore area per square meter of polyester base film surface is approximately 8.4m². 2 When the porosity of a 4.5μm polyester film is 50%, its pore size can be 150nm, and the micropore area per square meter of polyester film surface is approximately 8.1m². 2 When the porosity of a 4.5μm polyester film is 40%, its pore size can be 100nm, and the micropore area per square meter of polyester film surface is approximately 9.7m². 2 .
[0052] Preferably, the thickness of the polyester base film is 2μm to 20μm, for example, it can be 2μm, 3μm, 4μm, 4.5μm, 5μm, 6μm, 6.5μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, etc., but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0053] In a second aspect, the present invention provides a method for preparing an organic resin coated film as described in the first aspect, the method comprising the following steps:
[0054] (1) Mix organic resin, curing agent, inorganic filler, surfactant and solvent to obtain organic resin mixed slurry;
[0055] (2) The organic resin mixture is coated on one or both sides of the polyester base film, cured to form an organic resin coating, and the surface of the organic resin coating is roughened to obtain the organic resin coated film.
[0056] Preferably, the solvent in step (1) includes any one or a combination of at least two of the following: naphtha, methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone, methyl isobutyl ketone, methyl ethyl ketone, cyclohexanone, ethyl methoxyethyl acetate, butyl acetate, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, propylene glycol monomethyl ether acetate, carbitol acetate, butyl carbitol, propylene glycol methyl ether, γ-butyrolactone, and diisobutyl ketone. Its main function is to change the solid content of the organic resin mixture and adjust its viscosity.
[0057] Preferably, the solid content of the organic resin mixture in step (1) is 40% to 60%, for example, it can be 40%, 45%, 50%, 55%, 60%, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0058] Preferably, the viscosity of the organic resin mixture slurry in step (1) is 5000 mPa·s to 10000 mPa·s, for example, it can be 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, 10000 mPa·s, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable. Within this viscosity range, the slurry can be guaranteed to have good rheological properties and coating performance. If the viscosity is too low, it cannot be coated onto the surface of the polyester base film; if the viscosity is too high, the rheological properties are poor, which will lead to uneven coating.
[0059] As needed, the organic resin mixture in step (1) may also include other additives, such as any one or a combination of at least two of the following: curing accelerator, flame retardant, thickener, and defoamer.
[0060] Preferably, the heating system for curing in step (2) can be selected from, but is not limited to, an infrared heating system and / or a hot air circulation system.
[0061] Preferably, the curing in step (2) includes two processes: a first pre-curing stage and a second curing stage.
[0062] Preferably, the temperature of the first pre-curing stage is 80℃~100℃, for example, 80℃, 85℃, 90℃, 95℃, 100℃, etc., but not limited to the listed values; other unlisted values within this range are also applicable. The pre-curing time of the first stage is 20min~60min, for example, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min, 60min, etc., but not limited to the listed values; other unlisted values within this range are also applicable. The first pre-curing process allows the small molecules in the organic resin mixture to fully expand and achieve uniform distribution.
[0063] Preferably, the degree of curing of the coating formed after the first pre-curing stage is 40% to 70%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable. If the degree of curing after pre-curing is too low, the structure formed in the pre-curing stage is relatively loose, and the intermolecular cross-linking is insufficient. During the subsequent complete curing process, the stress distribution inside the coating may be uneven, resulting in a decrease in the mechanical properties of the coating. Moreover, the coating may undergo significant shrinkage during the subsequent complete curing process, leading to cracks or voids on the coating surface. If the degree of curing after pre-curing is too high, it means that the coating has formed a relatively dense structure during the pre-curing process. When it comes into contact with the polyester base film, the number of its active functional groups is relatively reduced, and a large number of epoxy groups react, which reduces the sites where chemical bonds can be formed between the coating and the substrate, thus leading to a decrease in adhesion. On the other hand, it will also lead to an overly dense cross-linked network. When the coating is subjected to external force bending or stretching, it is difficult for the molecular chains to slide or rearrange to adapt to this deformation. This makes the coating less flexible and prone to cracking under external forces such as bending or impact.
[0064] The degree of curing is characterized by the Knoop hardness test, H. c H represents the Knoop hardness of the surface after the organic resin coating has fully cured. p The degree of curing α, representing the Knoop hardness of an organic resin coating of the same composition after pre-curing, can be calculated using the following formula: .
[0065] Preferably, the curing temperature of the second stage is 170℃~200℃, for example, it can be 170℃, 175℃, 180℃, 185℃, 190℃, 195℃, 200℃, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable. The curing time of the second stage is 60min~90min, for example, it can be 60min, 65min, 70min, 75min, 80min, 85min, 90min, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable. The purpose of the second stage curing is to allow the small molecules in the organic resin mixture to undergo a cross-linking reaction after reaching the glass transition temperature, thus completing the curing process.
[0066] Preferably, the thickness of the organic resin coating on one side in step (2) is 1μm to 10μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc., but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0067] Preferably, the surface roughening treatment in step (2) includes any one or a combination of at least two of the following methods: wet chemical etching, plasma surface treatment, ultraviolet-ozone radiation surface treatment, and laser etching. After this surface roughening treatment, the average surface roughness of the organic resin coating in the organic resin coating film is controlled between 200 nm and 400 nm.
[0068] Thirdly, the present invention provides a composite current collector, the composite current collector comprising a coating film and conductive metal layers loaded on both sides of the coating film;
[0069] The coating film is the organic resin coating film described in the first aspect.
[0070] Preferably, the conductive metal layer is made of any one of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, and silver, with aluminum and / or copper being more preferred.
[0071] Preferably, the thickness of the conductive metal layer on one side is 1μm to 2μm, for example, it can be 1μm, 1.2μm, 1.3μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc., but it is not limited to the listed values, and other unlisted values within this range are also applicable. The greater the thickness of the conductive metal layer, the better the conductivity of the composite current collector, but its weight increases, which is not conducive to lightweighting and improving the energy density of lithium batteries; the smaller the thickness of the conductive metal layer, the lighter the composite current collector, but its conductivity decreases, its internal resistance increases, and the risk of thermal runaway increases.
[0072] Preferably, the loading method of the conductive metal layer can be selected from, but is not limited to, any one or a combination of at least two of vacuum magnetron sputtering coating, vacuum evaporation coating, vacuum plasma coating, electroless plating, and electroplating.
[0073] Preferably, when the conductive metal layer is aluminum, the preferred loading method for the conductive metal layer is vacuum evaporation coating.
[0074] Preferably, when the conductive metal layer is copper, the loading method of the conductive metal layer can be selected from the dry one-step method of vacuum evaporation coating, or the wet one-step method combining chemical plating and electroplating, or the two-step method combining vacuum magnetron sputtering coating and electroplating, or the two-step method combining vacuum magnetron sputtering coating and vacuum evaporation coating, or the three-step method combining vacuum magnetron sputtering coating, vacuum evaporation coating and electroplating.
[0075] Compared with the prior art, the present invention has the following beneficial effects:
[0076] (1) The organic resin coating film provided by the present invention has an organic resin coating on one or both sides of the polyester base film, which effectively reduces the thermal expansion coefficient and thermal shrinkage rate of the polyester base film and improves the thermal stability of the polyester base film. When used in composite current collectors, it can prevent problems such as base film wrinkling, shrinkage, breakage and conductive metal layer peeling caused by temperature changes during the preparation and use of composite current collectors, greatly improves the yield and production efficiency in the preparation process of composite current collectors, and can achieve cost reduction and efficiency improvement and large-scale mass production.
[0077] (2) In this invention, after the surface roughening treatment of the organic resin coating on the surface of the organic resin coating film, uniformly distributed holes are formed, further improving the average surface roughness of the organic resin coating film to the optimal range of 200nm~400nm. When used in composite current collectors, the conductive metal layer and the rough organic resin coating are combined to form an embedded "rivet" structure with higher peel strength.
[0078] (3) The organic resin coating film provided by the present invention is easier to deposit a conductive metal layer on the surface directly through a one-step electroplating process because the organic resin coating on the surface of the polyester base film is easier to be chemically roughened in the one-step electroplating process, which is conducive to the deposition of metal nanoparticles and improves the adhesion of the metal layer.
[0079] (4) The organic resin coating film and the conductive metal layer in the composite current collector prepared by the present invention are tightly bonded. The conductive metal layer is evenly and densely distributed, and has excellent uniformity, heat resistance, mechanical strength and corrosion resistance, with excellent comprehensive performance. Attached Figure Description
[0080] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below only relate to some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the content and drawings of the embodiments of the present invention without creative effort.
[0081] Figure 1 This is a scanning electron microscope image of the organic resin coating film provided in Embodiment 1 of the present invention.
[0082] Figure 2 This is a schematic diagram of the copper composite current collector provided in Embodiment 1 of the present invention;
[0083] Among them, 10-polyester base film; 11-organic resin coating; 12-conductive metal layer (copper layer); 20-spherical silica particles; 30-micropores on the surface of the original polyester base film layer; 31-larger micropores formed after roughening of the surface of the organic resin coating. Detailed Implementation
[0084] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.
[0085] Preparation Example 1
[0086] This preparation example provides spherical silica surface-treated with a silane coupling agent. The preparation method includes the following steps:
[0087] ① Solution preparation: Dissolve silane coupling agent KH560 in isopropanol to prepare a 3% solution;
[0088] ② Infiltration reaction: Spherical silica powder (Jiangsu Huimai, average particle size 150nm, specific surface area 35m²) 2 / g) is immersed in the prepared silane coupling agent solution, wherein the volume ratio of the spherical silica powder to the silane coupling agent solution is 1:4, and stirring is performed to ensure that the spherical silica powder can be fully wetted by the silane coupling agent solution. The treatment time is 30min.
[0089] ③ Filtration and drying: Filter out the silane coupling agent solution, and dry the treated spherical silica solid at 120℃ for 2 hours to remove the solvent on the surface;
[0090] ④ Curing: The dried spherical silica particles need to undergo curing treatment to ensure that the silane coupling agent forms stable chemical bonds with the particle surface. The curing temperature is set to 200℃ and the curing time is set to 2 hours.
[0091] Unless otherwise specified, the raw material information used in the following embodiments and comparative examples of the present invention is as follows:
[0092] Bisphenol AF type epoxy resin: Dow Chemical DER 351, epoxy equivalent 178;
[0093] Biphenyl-type epoxy resin: Mitsubishi Chemical YX4000, epoxy equivalent 195;
[0094] Naphthalene-type epoxy resin: Hunan Jiashengde NPTE4000, epoxy equivalent 330;
[0095] Aminophenol type epoxy resin: Mitsubishi Chemical 630LSD, epoxy equivalent 115;
[0096] o-Cresol-type phenolic epoxy resin: Nan Ya NPCN-704 from Taiwan, China, epoxy equivalent 210;
[0097] Linear phenolic epoxy resin: Nan Ya Plastics Group (Taiwan) NPEH-710HA65;
[0098] Phenolic curing agent: Ancamine 2757, Evonik Chemicals;
[0099] Reactive ester-based curing agent: Ancamine 2264, Evonik Chemicals;
[0100] Spherical silica surface-treated with a silane coupling agent: Preparation Example 1 provided;
[0101] Diethylaminomethyltriethoxysilane compound: Kaiyin Chemical.
[0102] Example 1
[0103] The first aspect of this embodiment provides an organic resin coated film, the preparation method of which includes the following steps:
[0104] (1) A BOPET membrane with a thickness of 4.5 μm, a porosity of 50%, and a pore size of 150 nm was used as the polyester base membrane (purchased from Toray Industries, South Korea) for later use.
[0105] (2) The organic resin mixture was prepared by the following method: 70 parts of bisphenol AF type epoxy resin and 35 parts of biphenyl type epoxy resin were heated and dissolved in 500 parts of methyl ethyl ketone while stirring. After cooling to room temperature, 20 parts of phenolic curing agent, 230 parts of spherical silica surface-treated with silane coupling agent (KH560) and 2 parts of diethylaminomethyltriethoxysilane compound were added to the mixture and dispersed uniformly in a high-speed rotary mixer to obtain an organic resin mixture with a viscosity of 6000 mPa·s.
[0106] (3) On a metal mold coating machine, the organic resin mixture prepared in step (2) is coated on both sides of the BOPET film prepared in step (1) by roller coating. It is pre-cured at 100°C for 30 min (the curing degree of the coating after pre-curing is 52%), and then dried and cured at 180°C for 60 min, so that the thickness of the organic resin coating on both sides of the BOPET film after drying is 2 μm.
[0107] (4) The organic resin coating obtained in step (3) is subjected to surface roughening treatment by laser etching (specific process parameters are: laser power: 30W, laser frequency: 50kHz, etching time: 20s) so that the average surface roughness Ra of the organic resin coating on both sides is 300nm, and the organic resin coating film is obtained. The surface roughening treatment further roughens the surface of the organic resin coating and improves the surface adhesion of the organic resin coating film.
[0108] The scanning electron microscope image of the organic resin coating film provided in this embodiment is as follows: Figure 1 As shown, by applying an organic resin coating to both sides of the polyester-based film and then roughening the surface of the organic resin coating, the average surface roughness of the film is significantly improved. The second aspect of this embodiment provides a copper composite current collector, specifically including the following steps:
[0109] (1) The organic resin coating film provided in the first aspect of this embodiment is selected as the carrier of metallic copper;
[0110] (2) A 50 nm thick copper underlay layer is deposited on both the upper and lower surfaces of the organic resin coating film by vacuum magnetron sputtering: the vacuum degree of the vacuum magnetron sputtering equipment cavity is 10. -3 Pa, the film winding tension was set to 80 N / m, the coating rate was set to 12 m / min, and a metallized BOPET film with a surface sheet resistance of 1 Ω / □ was obtained;
[0111] (3) The base copper layer of the metallized BOPET film is thickened by electroplating using a roller-type horizontal plating process. The metallized BOPET film is used as the cathode and the copper plate is used as the anode. The current density of the electroplating tank is increased from 0.5ASD to 5ASD. The copper ion concentration of the electroplating solution is maintained at 2mol / L and the plating rate is maintained at 10m / min. The process involves alkaline ion replacement, water washing, acidic ion replacement, anti-oxidation treatment and drying. A copper composite current collector with a thickness of 1μm is deposited on both base copper layers.
[0112] The structural schematic diagram of the copper composite current collector provided in this embodiment is as follows: Figure 2 As shown.
[0113] Examples 2-13, Comparative Examples 1-4
[0114] The only difference from Example 1 is that the type and / or parameters of the polyester base film, the formulation of the organic resin mixture slurry, the curing conditions, and the surface roughening treatment method were changed when preparing the organic resin coated film, as shown in Tables 1-3.
[0115] Table 1
[0116]
[0117] Table 2
[0118]
[0119] Table 3
[0120]
[0121] Test methods
[0122] The organic resin coated film and composite current collector provided in the embodiments and comparative examples of the present invention were tested using the following methods:
[0123] Surface microstructure: Observed and analyzed using a high-magnification scanning electron microscope.
[0124] Surface tension (dyne value): The surface dyne value of the organic resin coated film was tested according to GB / T 14216-2008.
[0125] Surface sheet resistance: The resistance was measured at five locations around and in the center of the composite current collector using a four-probe resistance tester, and the average value was taken.
[0126] Heat shrinkage rate test: The heat shrinkage rate test shall be conducted in accordance with the method of GB / T 13519-2008, and the test conditions shall be 150℃ / 1h.
[0127] Peel strength: Tested on a universal tensile testing machine and analyzed in accordance with the national standard GB / T 2792-2014.
[0128] Tensile strength & elongation at break: Tested according to national standard GB / T 16492-2008 on a tensile testing machine (model: EM6.202) of Metersbonwe Industrial Systems (China) Co., Ltd. A higher elongation at break indicates that the composite current collector is less likely to break and has better extensibility.
[0129] Puncture strength: Tested according to national standard GB / T 37841-2019 on a tensile testing machine (model: EM6.202) of Meters Industrial Systems (China) Co., Ltd. At least 5 specimens were cut for each sample for testing. The specimen size was 100mm×100mm, ensuring that they were flat, undamaged and without obvious defects. The specimens were laid flat in the fixture and clamped. The puncture resistance was tested at the selected puncture speed: (100±10)mm / min, and the puncture elongation was recorded as needed.
[0130] High-temperature resistance test: Keep in an oven at 150±5℃ for 24 hours and observe the deformation degree of the composite current collector and the peeling of the metal layer. If the deformation degree is ≤10% and there is no peeling of the metal layer, it is considered to pass the high-temperature test; otherwise, it is considered to fail.
[0131] Corrosion resistance test: Under normal temperature and pressure, the composite current collector sample is completely immersed in 1 mol / L PF6EC / DMC / DEC electrolyte for 72 hours, and the deformation, corrosion, and peeling of the sample are observed. If there is no deformation, no obvious corrosion, and no metal layer peeling, the corrosion resistance test is considered passed; otherwise, it is considered failed.
[0132] The test results of the organic resin coated films prepared in all embodiments and comparative examples of the present invention are shown in Table 4.
[0133] Table 4
[0134]
[0135] As can be seen from Table 4, the surface tension of the organic resin coated films provided in Examples 1-10 is significantly higher than that of the organic resin coated films provided in Examples 11-13 and Comparative Example 1. This is because coating the two surfaces of the polyester base film with organic resin layers according to the parameters defined in this invention, and then roughening the surface of the organic resin layers, significantly improves the average surface roughness of the polyester base film. This is evident from Table 4. Figure 1It can also be seen more intuitively that after coating with organic resin and undergoing surface roughening treatment, the average surface roughness is significantly improved, and the higher the roughness, the greater the surface tension of the coated film. Due to the excellent heat resistance and low coefficient of thermal expansion of epoxy resin, and by controlling the pre-curing process, the thermal shrinkage rate of the organic resin coated films provided in Examples 1-10 is significantly lower than that of the organic resin coated films provided in Examples 11-13 and Comparative Example 1. The thermal shrinkage rates of Examples 9 and 10 are even lower because the thermal shrinkage rates of PBT and PEN films are inherently significantly lower than those of BOPET films. After coating with an epoxy resin layer according to the parameters defined in this invention, the tensile strength and elongation at break of the polyester film are further improved. From the above analysis, it can be seen that applying organic epoxy resin to the surface coating modification of polyester base films can effectively solve the problems of low production yield, poor performance of composite current collectors, and high overall cost caused by low surface tension, poor heat resistance, easy wrinkling and shrinkage, and film breakage in the existing preparation process of composite current collectors based on polyester films.
[0136] The test results of the composite current collectors prepared in all embodiments and comparative examples of this invention are shown in Table 5.
[0137] Table 5
[0138]
[0139] As shown in Table 5, the physical properties of the composite current collector, such as peel strength, tensile strength, elongation at break, and thermal shrinkage, are positively correlated with the physical properties of the base film used. That is, the better the performance of the base film, the better the relevant properties of the prepared composite current collector. The test results show that the composite current collector obtained by coating the polyester base film with epoxy resin according to the parameters defined in this invention has lower surface sheet resistance and higher peel strength. This indicates that after loading the polyester base film with an organic resin coating and performing surface roughening treatment, the average surface roughness of the polyester base film is further improved to the optimal range, enhancing the adhesion of the base film surface and making it more conducive to the deposition and adhesion of metal particles, effectively improving the uniformity and adhesion of the metal conductive layer. Compared with Examples 11-13 and Comparative Examples 1-4, the composite current collectors prepared in Examples 1-10 of this invention have higher metal layer peel strength and mechanical strength, lower thermal shrinkage at 150℃ / 1h, and all passed the high-temperature resistance test and electrolyte corrosion resistance test, indicating that the epoxy resin coating within the scope defined in this invention effectively improves the heat resistance and corrosion resistance of the base film. The test results above all prove the feasibility of the present invention: by coating the surface of the polyester base film with an organic resin coating and roughening it, the thermal stability, corrosion resistance and surface adhesion of the polyester base film can be improved, thereby solving the problems of low production yield and high overall cost caused by poor heat resistance, easy wrinkling and poor corrosion resistance of the base film in the preparation of existing composite current collectors based on polyester base films, as well as the industry pain points of composite current collectors prepared from such base films, such as easy metal layer peeling, poor structural stability, poor high temperature resistance and poor resistance to electrolyte corrosion.
[0140] The applicant declares that the above embodiments illustrate the organic resin coating film, its preparation method, and its application. However, the present invention is not limited to the above embodiments, meaning that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, additions of auxiliary components, and selection of specific methods all fall within the protection and disclosure scope of the present invention.
Claims
1. An organic resin coated film, characterized in that, The organic resin coated film includes a polyester base film and an organic resin coating disposed on one or both sides of the polyester base film. The organic resin coating comprises organic resin, curing agent, inorganic filler, and surfactant; The average surface roughness Ra of the organic resin coating is 200 nm to 400 nm.
2. The organic resin coated film according to claim 1, characterized in that, The organic resin includes any one or a combination of at least two of epoxy resin, acrylic resin, hydrocarbon resin, triazine resin, polytetrahydrofuran resin, fluororesin, phenoxy resin, polyvinyl acetal resin, polyimide resin, polyamide-imide resin, polysiloxane resin, polyether-imide resin, polysulfone resin, polyethersulfone resin and polyphenylene ether resin, preferably epoxy resin. Preferably, the organic resin accounts for 20% to 40% of the total mass of the organic resin coating.
3. The organic resin coated film according to claim 2, characterized in that, The epoxy resin includes at least two of the following: bisphenol type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, phenol type epoxy resin, and phenolic type epoxy resin. Preferably, based on the total mass of the epoxy resin as 100%, the proportion of bisphenol type epoxy resin is 40%~75%, the proportion of biphenyl type epoxy resin is 5%~40%, the proportion of naphthalene type epoxy resin is 0%~35%, the proportion of phenol type epoxy resin is 0%~40%, and the proportion of phenolic type epoxy resin is 0%~50%.
4. The organic resin coated film according to any one of claims 1-3, characterized in that, The curing agent includes any one or a combination of at least two of the following: phenol-based curing agents, naphthol-based curing agents, reactive ester-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, and carbodiimide-based curing agents; Preferably, the curing agent accounts for 5% to 10% of the total mass of the organic resin coating.
5. The organic resin coated film according to any one of claims 1-4, characterized in that, The inorganic filler includes any one or a combination of at least two of the following: silica, alumina, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, calcined kaolin, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, titanium dioxide, silicon carbide, and zirconium oxide, preferably silica. Preferably, the average particle size of the inorganic filler is 50nm~350nm, more preferably 100nm~200nm; Preferably, the inorganic filler accounts for 50% to 80% of the total mass of the organic resin coating, which is 100%.
6. The organic resin coated film according to any one of claims 1-5, characterized in that, The surfactant includes any one or a combination of at least two of aminosilane compounds, aminosiloxane compounds, alkylsilane compounds, and alkylsiloxane compounds; Preferably, the surfactant comprises a diethylaminomethyltriethoxysilane compound; Preferably, the surfactant accounts for 0.5% to 2% of the total mass of the organic resin coating, which is 100%.
7. The organic resin coated film according to any one of claims 1-6, characterized in that, The polyester-based film is made of any one or a combination of at least two of the following materials: polyterephthalate, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyurethane, polyurethane, polyvinyl acetate, polyarylate, polyethylene naphthalate, polyethylene oxide acrylate, polycarbonate, thermoplastic polyester elastomer, polybutylene succinate, and polycaprolactone. Preferably, the porosity of the polyester-based film is 20%~70%, more preferably 40%~60%; Preferably, the pore size of the polyester-based film is 50 nm to 300 nm; Preferably, the thickness of the polyester base film is 2μm to 20μm.
8. A method for preparing an organic resin coated film as described in any one of claims 1-7, characterized in that, The preparation method includes the following steps: (1) Mix organic resin, curing agent, inorganic filler, surfactant and solvent to obtain organic resin mixed slurry; (2) The organic resin mixture is coated on one or both sides of the polyester base film, cured to form an organic resin coating, and the surface of the organic resin coating is roughened to obtain the organic resin coated film.
9. The preparation method according to claim 8, characterized in that, The solvent in step (1) includes any one or a combination of at least two of the following: naphtha, methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone, methyl isobutyl ketone, methyl ethyl ketone, cyclohexanone, methoxyethyl acetate, ethyl acetate, butyl acetate, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, propylene glycol monomethyl ether acetate, carbitol acetate, butyl carbitol, propylene glycol methyl ether, γ-butyrolactone, and diisobutyl ketone; Preferably, the solid content of the organic resin mixture in step (1) is 40%~60%; Preferably, the viscosity of the organic resin mixture slurry in step (1) is 5000 mPa·s to 10000 mPa·s; Preferably, the heating system for curing in step (2) can be selected from, but is not limited to, an infrared heating system and / or a hot air circulation system; Preferably, the curing in step (2) includes two processes: a first pre-curing stage and a second curing stage. Preferably, the temperature of the first pre-curing stage is 80℃~100℃, and the pre-curing time of the first stage is 20min~60min; Preferably, the degree of curing of the coating formed after the first pre-curing stage is 40% to 70%. Preferably, the curing temperature of the second stage is 170℃~200℃, and the curing time of the second stage is 60min~90min; Preferably, the thickness of the organic resin coating on one side in step (2) is 1 μm to 10 μm; Preferably, the surface roughening treatment in step (2) includes any one or a combination of at least two of the following methods: wet chemical etching, plasma surface treatment, ultraviolet-ozone radiation surface treatment, and laser etching.
10. A composite current collector, characterized in that, The composite current collector includes a coating film and conductive metal layers loaded on both sides of the coating film; The coating film is the organic resin coating film according to any one of claims 1-7; Preferably, the conductive metal layer is made of any one of copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, titanium, and silver, with aluminum or copper being preferred. Preferably, the thickness of the conductive metal layer on one side is 1μm to 2μm.